2023
DOI: 10.3348/kjr.2022.0898
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Strain Derived From Cardiac Magnetic Resonance Imaging Can Predict Outcomes of Patients With Acute Myocarditis

Abstract: Objective There is increasing recognition that left atrial (LA) strain can be a prognostic marker of various cardiac diseases. However, its prognostic value in acute myocarditis remains unclear. Therefore, this study aimed to evaluate whether cardiovascular magnetic resonance (CMR)-derived parameters of LA strain can predict outcomes in patients with acute myocarditis. Materials and Methods We retrospectively analyzed the data of 47 consecutive patients (44.2 ± 18.3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Meindl et al investigated the diagnostic value of LV and LA myocardial strains in AM patients with preserved EF using speckle tracking echocardiography, demonstrating reservoir and conduit dysfunction in patients with acute myocarditis compared to healthy controls [23]. Similarly, Lee et al showed impaired reservoir and conduit mechanisms in AM patients using CMR [28]. Our data confirmed these results, supporting the hypothesis of abnormalities in atrial compliance and diastolic impairment throughout the course of AM, despite preserved EF.…”
Section: Discussionsupporting
confidence: 88%
“…Meindl et al investigated the diagnostic value of LV and LA myocardial strains in AM patients with preserved EF using speckle tracking echocardiography, demonstrating reservoir and conduit dysfunction in patients with acute myocarditis compared to healthy controls [23]. Similarly, Lee et al showed impaired reservoir and conduit mechanisms in AM patients using CMR [28]. Our data confirmed these results, supporting the hypothesis of abnormalities in atrial compliance and diastolic impairment throughout the course of AM, despite preserved EF.…”
Section: Discussionsupporting
confidence: 88%